Transcriptome and selected metabolite analyses reveal points of sugar metabolism in jackfruit (Artocarpus heterophyllus Lam.). (July 2016) - Hu, Lisong; Wu, Gang; Hao, Chaoyun; Yu, Huan; Tan, Lehe
Highlights: A perianth trancriptome of Jackfruit was sequenced on Illumina HiSeq 2500 platform. The internal control gene for normalization of gene expression was identified. The characterization of sugar metabolism in Jackfruit was studied by transcriptome and selected metabolites analysis. Abstract: Artocarpus heterophyllus Lam., commonly known as jackfruit, produces the largest tree-borne fruit known thus far. The edible part of the fruit develops from the perianths, and contains many sugar-derived compounds. However, its sugar metabolism is poorly understood. A fruit perianth transcriptome was sequenced on an Illumina HiSeq 2500 platform, producing 32, 459 unigenes with an average length of 1345 nt. Sugar metabolism was characterized by comparing expression patterns of genes related to sugar metabolism and evaluating correlations with enzyme activity and sugar accumulation during fruit perianth development. During early development, high expression levels of acid invertases and corresponding enzyme activities were responsible for the rapid utilization of imported sucrose for fruit growth. The differential expression of starch metabolism-related genes and corresponding enzyme activities were responsible for starch accumulated before fruit ripening but decreased during ripening. Sucrose accumulated during ripening, when the expression levels of genes for sucrose synthesis were elevated and high enzyme activity was observed. The comprehensive transcriptome analysis presents fundamental information on sugar metabolism and will be a useful reference for further research on fruit perianth development in jackfruit.